2015
DOI: 10.1002/ente.201402138
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Delignification of Biomass for Enhanced Fermentable Sugars Production

Abstract: The United Arab Emirates (UAE) has more than 40 million palm trees producing approximately 15 kg of waste fronds per tree. These fronds contain a large portion of polysaccharides, which can be hydrolyzed to simple fermentable sugars. Seaweed consists of macroalgae containing high portions of polysaccharides, which are also abundantly found on the coasts of UAE. The effectiveness of lignin to degrade enzymes for the pretreatment of biomass from palm trees fronds and indigenous seaweed (prior to enzymatic hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The lignin removal obtained in this study is higher than those reported using commercial laccases or in laccase association with other pretreatment methods (Table 4). Al-Zuhair et al, (2015) [31] stated 9% of delignification with commercial Trametes versicolor laccase using HBT (hydroxybenzotriazole) as mediator. Rencoret et al, (2019) described 24% of lignin removal from Paulownia fortune after laccase-mediated pretreatment combined with alkaline extraction with NaOH [32], while Gutiérrez et al, (2012) reported up to 32% reduction in lignin content for Elephant grass applying the same combine pretreatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…The lignin removal obtained in this study is higher than those reported using commercial laccases or in laccase association with other pretreatment methods (Table 4). Al-Zuhair et al, (2015) [31] stated 9% of delignification with commercial Trametes versicolor laccase using HBT (hydroxybenzotriazole) as mediator. Rencoret et al, (2019) described 24% of lignin removal from Paulownia fortune after laccase-mediated pretreatment combined with alkaline extraction with NaOH [32], while Gutiérrez et al, (2012) reported up to 32% reduction in lignin content for Elephant grass applying the same combine pretreatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…The peaks at 16° and 23° reflect crystalline cellulose type I, while cellulose type II is presented at 20°. The intensity of those peaks increased in both full-pretreatment and lignin-removed DSs biomass, which indicates a higher crystallinity degree in the structure of the treated fibers due to the removal of lignin [ 25 ]. A similar increase in the intensity of peaks that represent crystalline cellulose was also observed with DSs from Phoenix dactylifera L. after lignin and hemicellulose removal [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…158 Al-Zuhair et al investigated the enzymatic delignification of seaweed biomass (a mix of Chaetomorpha and Cladophora species), carried out using TvL, HBT, and [EMIM][OAc] obtaining a delignification degree up to 27%. 162 Rezaei et al reported the use of LC from the halophilic bacterium Aquisalibacillus elongatus in the presence of [BMIM]-[PF 6 ] (1-butyl-3-methylimidazolium hexafluorophosphate) to delignify sugar beet pulp, obtaining a delignification yield of 78.4% after 24 h. 163 The same enzyme was also tested in the same conditions in [BMIM][PF 6 ] to remove lignin from peanut shell, obtaining a lignin removal of 87% after 24 h. 164 Deep Eutectic Solvents. Deep eutectic solvents (DESs) are a new class of green solvents composed of a hydrogen bond acceptor (HBA, usually a quaternary ammonium salt) and a hydrogen bond donor (HBD) such as glycerol, succinic acid, etc.…”
Section: Acs Sustainablementioning
confidence: 99%
“…They obtained a final lignin content of about 8.5 wt %, compared to the initial 24.0 wt % of untreated OPFB . Al-Zuhair et al investigated the enzymatic delignification of seaweed biomass (a mix of Chaetomorpha and Cladophora species), carried out using TvL, HBT, and [EMIM]­[OAc] obtaining a delignification degree up to 27% . Rezaei et al reported the use of LC from the halophilic bacterium Aquisalibacillus elongatus in the presence of [BMIM]­[PF 6 ] (1-butyl-3-methylimidazolium hexafluorophosphate) to delignify sugar beet pulp, obtaining a delignification yield of 78.4% after 24 h .…”
Section: Delignification Main Strategies and Protocolsmentioning
confidence: 99%